-the Five Major Factors Of Personality For Teachers Of Physical And Sports Education -a Field Study On Some Middle Schools Of Laghouat - Mechid , Yacine (sports creativity, 2025)
This study aimed to know the personality trait that most influences teachers of physical and sports education, and the study survey included 59 teachers in the middle school cycle, and the survey was chosen in a random manner as we employed the descriptive approach which was used in data collection to measure the five major factors model of the personality of Costa and McCrae 1992. The results of this approach proved that: -the teachers of physical and sport characterized by high level of five major factors of personality. - the conscientiousness is the most influential among teachers of physical and sports education for some middle schools in the state of Laghouat